Dispositivos e subjetivação: representações sobre violência doméstica da rede de proteção às mulheres no município de Enéas Marques. - Cattâneo, Jussandra Cardoso Moreira (2024)
This study was conducted within the scope of the Graduate Program in Education - Master's, at the Francisco Beltrão Campus, Paraná, at the State University of Western Paraná - Unioeste. The program's area of concentration is Education, within the Research Line "Culture, Educational Processes, and Teacher Training." The general objective of the research was to analyze the representations of domestic violence against women that appear and are reflected in the statements of individuals working in the protection and response network in the municipality of Enéas Marques/PR. The specific objectives were defined as follows: (i) to identify the dynamics of the services provided by the protection network against domestic violence towards women in the municipality of Enéas Marques; (ii) to understand the representations of gender and domestic violence held by individuals who make up the response network in Enéas Marques/PR; (iii) to recognize the devices that shape subjectivity in the construction of being a man and being a woman for the interviewed individuals; and (iv) to describe the process of implementing the Women’s Social Center in Enéas Marques as a space for creating educational actions and public policies to defend women’s rights. The text is organized into the following sections: I - Theoretical-Methodological Choices: Research Paths; II - Devices and Domestic Violence Against Women: Reception and Perplexities; III - Network Work: Discourses and Subjectivities. The final considerations appear under the title IV - Of Inconclusions: Networks in Motion. The research was developed around the following question: What are the representations of domestic violence against women held by individuals working in the domestic violence response network in the municipality of Enéas Marques/PR? We chose the following complementary question: What gender devices are present in the discourses of individuals who work in the domestic violence response and protection network in Enéas Marques? The study understood that subjectivities are constructed through social relations and that, consequently, gender violence arises in relations of power and knowledge, in devices and technologies. The theoretical references are philosophical, based on Foucault's genealogy studies (1979) and gender issues informed by feminist theorists such as Butler (2005), Louro (2000, 2023), and Zanello (2018). This investigation was qualitative, employing a Case Study approach, with semi-structured interviews, document analysis, and descriptions of actions carried out within public policies implemented in the municipality of Enéas Marques as research instruments. As a result of the investigation, it can be stated that the representations of the interviewed individuals indicate the following points: the dynamics of services present in the municipality were identified, and the representations of the individuals suggest both reception and support for women experiencing domestic violence. We conclude that the individuals are aware of the devices that shape the subjectivities of both women and men and of their consequences in gender relations. Finally, graphical materials were produced to present the flow that makes up the protection network in the municipality of Enéas Marques.